Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Membuat Pola dan Teknik Menjahit - Maghfiroh, Fachrial Lailatul; Nurrokhim, Isma; Mahmud, Ali; Toyibatussalamah, Toyibatussalamah; Widiasari, Susi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Sewing training is one of the effective solutions to empower housewives to be more economically independent. This activity is motivated by the need to improve women's skills in the field of sewing, which can open up small business opportunities, both as home convection and sewing services. By collaborating with Indonesian Taylor as a training partner, this training activity is designed to provide an understanding of basic pattern making and sewing techniques. The training was attended by 10 housewives, held once a week with different locations to maintain participant enthusiasm. The implementation method includes providing theoretical material, pattern making practice, and basic sewing techniques. Mentoring is carried out intensively to ensure that participants can master the skills taught. The results of the activity showed a significant increase in participants' abilities in making simple patterns and sewing. In addition, participants felt motivated to start a small business in the field of home convection. This program has succeeded in providing new skills that are relevant to the economic needs of participants and have the potential to increase family income.